PENYULUHAN HUKUM PERUBAHAN STATUS HAK GUNA BANGUNAN MENJADI HAK MILIK - Satrio Abdillah; Saiful Anwar Reza; Mardayan Arifandi; Reflyna Karnesih (Marsialapari: Jurnal Pengabdian Kepada Masyarakat, 2025)
This study aims to analyze the process of changing the status of Building Use Rights (HGB) to Ownership Rights (HM) in Merjosari Village, Lowokmaru District, Malang City. This study uses a qualitative approach with a descriptive research type, where data is collected through in-depth interviews and participatory observation. The results of the study indicate that the lack of public understanding of legal procedures related to changes in land status is one of the main obstacles in the process. In addition, administrative obstacles such as long processing times and complex requirements were also found to be significant obstacles. This study provides recommendations regarding the importance of legal counseling and improving the administrative system to accelerate the process of changing land rights status. With the change in status of HGB to HM, landowners will obtain full ownership which provides more freedom in managing and transferring land.